USING TWO STAY-TWO STRAY TECHNIQUE TO IMPROVE STUDENTS' WRITING SKILLS - Zidni Tadzkiah, - (2018)
Previous studies on writing invented problems including difficulty in generating ideas, lack of vocabularies, and grammatical errors. The present research was aimed to describe how the use of two stay-two stray technique in the independent construction stage improves students' writing skills and find out the students' responses toward the advantages and barriers of the technique. A qualitative case study was employed to collect data with classroom observation, students' works, and interview. The results of the research revealed that the use of two stay-two stray technique in the independent construction stage indicate to help students in writing text. Moreover, students were likely to show positive responses as the technique has helped them collaborates with their friends and makes their writing better.